Penangkaran Kunang-Kunang Sebagai Konservasi Berbasis Masyarakat Di Desa Jladri - Jati Sumarah; Dimas Aditia Firmansya; Sotya Partiwi Ediwidjojo; Wenny Marlini; Ajeng Tiara Wulandari; Ari Waluyo; Laelil Rachma Fadhila; Intan Nur Azizah; M. Haikal Ramdani; Duke Sabella; Dewi Septian Endang Rahmawati; Agustina Ananda Pratiwi; Dwi Khoirul Anam; Imam Maulana; Syifa Nur Afiatun Khoiriyah (Politeknik Piksi Ganesha Indonesia, 2025)
The decline in firefly populations in Indonesia, including in Jladri Village, is caused by factors such as habitat changes, light pollution, and land conversion. Fireflies play an important role in the ecosystem as bioindicators of environmental quality and natural pollinators. Therefore, conservation efforts are needed that involve the community as the main actor in preserving this species. This community service aims to build a firefly breeding center in Jladri Village as part of community-based conservation efforts. The community service will include the establishment of a firefly breeding center by creating and maintaining a natural habitat that supports the survival of fireflies, as well as training the community on environmental management and reducing light pollution. By involving the community in every stage of the activity, it is hoped that they can have a high sense of ownership of firefly conservation